Pengaruh Fomo Marketing dan Sales Promotion Terhadap Online Impulsive Buying dengan Mediasi Retargeted Advertisements (Studi Pada Mahasiswa FISIP UPN “Veteran” Jawa Timur) - Mainun, Ihtadat Alam Makarima; Azizah, Nurul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to analyze the influence of Fomo Marketing, Sales Promotion, and Retargeted Advertisement on Online Impulsive Buying behavior among Shopee e-commerce users, especially students at the Faculty of Social and Political Sciences, East Java "Veteran" National Development University. This research uses a quantitative approach with an associative type of research. Data collection was carried out through an online questionnaire with a sample of 150 respondents. The data analysis technique used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) method. The research results show that Fomo Marketing has no significant effect on Online Impulsive Buying, while Sales Promotion and Retargeted Advertisement have a significant effect on Online Impulsive Buying. Retargeted Advertisement also mediates the effect of Sales Promotion on Online Impulsive Buying (partial mediation), but does not mediate the effect of Fomo Marketing on Online Impulsive Buying. The variable that has the most influence on Online Impulsive Buying is Retargeted Advertisement, followed by Sales Promotion, then Fomo Marketing. This research provides theoretical implications in increasing knowledge regarding the relationship between variables, as well as practical implications for companies in increasing sales through appropriate marketing strategies.